2003
DOI: 10.1034/j.1600-0714.2003.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral nicorandil‐induced lesions are not aphthous ulcers

Abstract: Oral nicorandil-induced lesions are not aphthous ulcers. We propose that at this stage of our knowledge, oral nicorandil-induced ulcer is the most suitable terminology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 5 publications
1
10
0
3
Order By: Relevance
“…A case-control study associated a higher risk of RAS with drug exposure and found significant association with nonsteroidal anti-inflammatory drugs and betablockers 70 . Nicorandil, a vasodilator used extensively outside the United States to manage angina as well as caclineurin and mTOR inhibitors used as immunosuppressors have been associated with severe aphthous-like ulcers 8,9,71 . Therefore, it is imperative to closely scrutinize the medication history as well as current medications of RAS patients to identify any pattern associated with frequency and duration of RAS lesions.…”
Section: Other Factorsmentioning
confidence: 99%
“…A case-control study associated a higher risk of RAS with drug exposure and found significant association with nonsteroidal anti-inflammatory drugs and betablockers 70 . Nicorandil, a vasodilator used extensively outside the United States to manage angina as well as caclineurin and mTOR inhibitors used as immunosuppressors have been associated with severe aphthous-like ulcers 8,9,71 . Therefore, it is imperative to closely scrutinize the medication history as well as current medications of RAS patients to identify any pattern associated with frequency and duration of RAS lesions.…”
Section: Other Factorsmentioning
confidence: 99%
“…An overall prevalence of 10-20% has been reported for the general population (Rennie et al, 1985;Scully et al, 2003), with a higher prevalence of RAS (56%) in selected groups, such as university students (Donatsky, 1973). Although hereditary (Ship, 1965;Shohat-Zabarski et al, 1992), dietary (Eversole, 1994), hematologic (Burgan et al, 2006), infectious (Barile et al, 1963;Sun et al, 1996), allergic (Boulinguez et al, 2003) and immunologic (Natah et al, 2000) factors have been implicated, their role as the main etiological factors in the pathogenesis remains to be elucidated. Furthermore, with the dramatic worldwide increase in patients with immuno-suppression caused by medical treatments, systemic diseases, or both, the prevalence of these conditions may be increasing.…”
Section: Introductionmentioning
confidence: 95%
“…Pour certains auteurs, il se différencie de celui des aphtes vrais par leur étendue et leur profondeur plus importantes [11,12]. Une étude de Boulinguez et al [17], menée auprès de 60 dermatologues, interrogés sur leur hypothèse diagnostique devant des photographies d'ulcérations buccales, a montré que seulement 71,8 % d'entre eux qualifiaient des ulcé-rations dues au nicorandil comme non aphteuses ; pour le reste des praticiens, les lésions étaient des aphtes typiques. Les trois critères cliniques qui permettaient aux praticiens de classer les ulcérations dues au nicorandil comme non aphtoïdes étaient : l'absence du fond jaune, la forme linéaire et l'absence du halo rouge péri-lésionnel [17].…”
Section: Discussionunclassified
“…Une étude de Boulinguez et al [17], menée auprès de 60 dermatologues, interrogés sur leur hypothèse diagnostique devant des photographies d'ulcérations buccales, a montré que seulement 71,8 % d'entre eux qualifiaient des ulcé-rations dues au nicorandil comme non aphteuses ; pour le reste des praticiens, les lésions étaient des aphtes typiques. Les trois critères cliniques qui permettaient aux praticiens de classer les ulcérations dues au nicorandil comme non aphtoïdes étaient : l'absence du fond jaune, la forme linéaire et l'absence du halo rouge péri-lésionnel [17]. Toutefois, les ulcérations dues au nicorandil présentaient un fond jaune dans 21 % des cas, une forme arrondie dans 66 % des cas, et étaient entourées d'un halo inflammatoire dans 42 % des cas [17], ce qui montre l'impossibilité de définir un aspect clinique caractéristique permettant de discriminer les deux pathologies.…”
Section: Discussionunclassified
See 1 more Smart Citation